2016
DOI: 10.1590/1983-084x/15_178
|View full text |Cite
|
Sign up to set email alerts
|

Germinação de sementes e emergência de plântulas de jutaí (Hymenaea parvifolia Huber.)

Abstract: Recebido para publicação em 29/09/2015 Aceito para publicação em 02/01/2016 RESUMO: O objetivo do presente trabalho foi avaliar a influencia do tamanho e da temperatura na germinação das sementes, assim como, da posição de escarificação do tegumento e a profundidade de semeadura na emergência de plântulas de jutaí. As sementes foram separadas em três grupos: sementes pequenas, médias e grandes. A germinação das sementes foram realizadas nas temperaturas de 5, 10, 15, 20, 25, 30, 35, 40 e 45 °C e com fotoperíod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
2
2
0
3
Order By: Relevance
“…These results are in agreement with Silva and Cesarino (2016) who observed that the number of leaves, height and length of roots of Jutaí seedlings decreased linearly with the sowing depth increase.…”
Section: Controlled Environmentsupporting
confidence: 93%
“…These results are in agreement with Silva and Cesarino (2016) who observed that the number of leaves, height and length of roots of Jutaí seedlings decreased linearly with the sowing depth increase.…”
Section: Controlled Environmentsupporting
confidence: 93%
“…This process allowed the entry of water and oxygen, in addition to favoring the action of hydrolytic enzymes that act with the activation of protein synthesis, enabling the mobilization of reserves from the germination process, as seen by Santos et al (2019), who obtained 93% seed germination from H. courbaril when subjected to mechanical scarification. This was also seen by other authors, such as Coelho and Ribeiro (2018), above 93%, Cabral, Castilho and Pagliarini (2015), above 86%, Sampaio et al (2015), with 84%, Souza et al (2015), above 80%, and by Silva and Cesarino (2016) with 69.2%. * Means followed by letters of the same lowercase letter horizontally and uppercase vertically do not differ, according to the Tukey test at 5%.…”
Section: Resultssupporting
confidence: 75%
“…It is known that the success in seed emergence is related not only to intrinsic factors, but also to the set of extrinsic and intrinsic factors acting concomitantly. This fact can be corroborated by the study done by Silva and Cesarino (2016), in which the authors studied the influence of different temperatures on the emergence of 'Jutaí' seeds (Hymenae aparvifolia Huber. ), obtaining different percentages and speed of emergence.…”
Section: Resultsmentioning
confidence: 65%